Body Contouring Surgery and the Maintenance of Weight-Loss Following Roux-En-Y Gastric Bypass: A Retrospective Study. (4th October 2017) - Smith, Oliver J; Hachach-Haram, Nadine; Greenfield, Max; Bystrzonowski, Nicki; Pucci, Andrea; Batterham, Rachel L; Hashemi, Majid; Mosahebi, Afshin
Abstract: Background: Bariatric surgery leads to significant weight loss with reduced morbidity and mortality. However, excess skin as a consequence of weight loss represents a major problem, impacting upon patient's functionality with potential negative effects on weight loss. Objectives: We evaluated the effect of body-contouring surgery on weight-loss maintenance following bariatric surgery. Methods: We undertook a retrospective analysis of patients undergoing Roux-en-Y gastric bypass (RYGB) +/- body-contouring surgery (BC). The control group (n = 61) received RYGB, the test group (n = 30) received RYGB+BC 12 to 18 months after bariatric surgery. Each RYGB+BC patient was matched to two control patients for age, sex, glycaemic status, and weight on day of surgery. Per cent weight loss (%WL) was calculated at 3, 6, 12, 24, 36, 48, and 60 months post-RYGB for both groups. Results: The %WL was similar at 3, 6, and 12 months post-RYGB. At 24 months, %WL was 35.6% in the RYGB+BC group and 30.0% in the RYGB group ( P < 0.05). At 36 months, the RYGB+BC group maintained their weight loss (%WL 33.0%), in contrast, the RYGB gained weight (%WL = 27.3%, P < 0.05). This trend continued (RYGB+BC vs RYGB) at 48 months (%WL 30.8% vs 27.0%) and at 60 months (%WL 32.2% vs 22.7%, P < 0.05). Conclusions: Our results suggest patients who undergo body contouring after bariatric surgery are able to lose significantly more weight and maintain weight loss at five years of follow up compared to those undergoing bariatric surgery alone. Level of Evidence: 3: